The mirror preference test: A reverse translational approach to study anomalous subjective experience in rats - Daria Chestnykh; Liubov S. Kalinichenko; Stephan von Hörsten; Johannes Kornhuber; Christian P. Müller (Brain Research Bulletin)
Significant advancements have been made in the treatment of psychotic disorders, yet current pharmacotherapy remains inadequate. Symptoms related to the misinterpretation of reality are crucial for diagnosis but pose challenges for preclinical research. In humans, a Mirror-Gazing test is used to examine abnormal self-experience and to predict the risk of schizophrenia. To address this, we developed a task to evaluate anomalous subjective experiences in rats using a Mirror-Preference test. Here we demonstrate that naive rats show a preference for a mirror chamber, which was followed by significant habituation over a series of trials. In subsequent tests, we utilized dimmed lighting and net-covered mirrors to induce incomplete mirror images. Acute stimulation with amphetamine (AMPH, 3 mg/kg, i.p.) further increased the preference for the mirror. In a model of psychosis induced by chronic AMPH administration, rats showed fewer and shorter interactions with the mirror but maintained their preference for the chamber where psychotic-like animals were given additional AMPH stimulation (1.5 mg/kg, i.p.) before testing. Here, a surprising reversal in chamber preference was observed, along with decreased frequency and duration of mirror contact, suggesting mirror avoidance. The AMPH-presensitized rats also exhibited hyperlocomotion and elevated anxiety, indicative of psychotic-like behaviour. Although self-recognition in rodents is debatable, recent studies suggest they can discriminate mirror images. We propose that limited visual perception that meets brain monoamine sensitization may trigger visual illusions as part of a psychotic-like state in rats. This novel approach can be utilized to test intervention strategies for psychosis in rats.